The Role of Media References During Public Deliberation Sessions. (April 2015) - Capurro, Gabriela; Dag, Haluk; Longstaff, Holly; Secko, David M.
One intrinsic component of public engagement events on scientific issues that has been ignored is the role of media representations as informational inputs. This is despite inferences that media representations may support learning, reflection, misinformation, or polarization during an event. In this article, we examined the role of media references during a public deliberation on advanced biofuels, revealing how participants used them for various purposes, such as supporting their points of view, challenging others, and adding information to the discussion. However, media references steadily decreased over time, and our analysis revealed that they ultimately had a limited influence on deliberations.